2019
DOI: 10.1002/jclp.22869
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events during a disorder‐specific psychotherapy compared to a nonspecific psychotherapy in patients with chronic depression

Abstract: Objectives A recent trial comparing Cognitive Behavioral Analysis System of Psychotherapy (CBASP) and supportive psychotherapy in chronic depression found CBASP to be more effective in treating depressive symptoms. We aimed to evaluate adverse events that occurred during this trial. Materials and Method A randomized trial of chronically depressed outpatients was performed. The treatment included 32 sessions of CBASP or supportive psychotherapy. Therapists asked patients about adverse events and their intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In general, adverse event methods seem to be heterogeneous and insufficiently reported in RCTs in CD ( 49 ). However, a recent study found that patients receiving supportive psychotherapy reported less severe adverse events in general and less severe adverse events related to personal life and to occupational life than patients receiving CBASP, while less adverse events related to suicidal thoughts were reported in CBASP compared with supportive psychotherapy ( 50 ). The authors discussed that the differences in the profile of adverse events may be explained by specific treatment elements, as adverse events related to personal and professional life, for example, may be considered a necessary and expected but temporary adverse treatment outcome of effective CBASP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In general, adverse event methods seem to be heterogeneous and insufficiently reported in RCTs in CD ( 49 ). However, a recent study found that patients receiving supportive psychotherapy reported less severe adverse events in general and less severe adverse events related to personal life and to occupational life than patients receiving CBASP, while less adverse events related to suicidal thoughts were reported in CBASP compared with supportive psychotherapy ( 50 ). The authors discussed that the differences in the profile of adverse events may be explained by specific treatment elements, as adverse events related to personal and professional life, for example, may be considered a necessary and expected but temporary adverse treatment outcome of effective CBASP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…net/ 1-glossary). Our semi-structured interview is an improvement on current GCP procedures in that most clinical trials assess the SAE variable based on patients spontaneous reports (for an example in psychotherapy research, see Meister et al 45 ). However, the SAE assessment has not been psychometrically validated yet.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Second, the e cacy of psychological counselling depends on the clinical communication and utilization of hybrid skills of the practicing psychologists [14][15][16]. Third, few studies have described any adverse event data of psychological counselling, although the dropout rate is known to be high according to previous research [17,18]. Therefore, an understanding of cancer patients' needs around counselling is still needed to provide a more effective treatment method for their psychological distress.…”
Section: Introductionmentioning
confidence: 99%